Self-esteem and loneliness as predicting factors of Arab children achievement İn Kuala Lumpur - al-Hoot, Asma'a; Ssekamanya, Siraje Abdallah (EUSEUR Pulishing, 2015)
Taking into consideration the fact that self-esteem and loneliness have an even more important role to play in students' learning, this study seeks to examine the correlation of these two factors with children academic performance. The study involved 499 (grade 4 to grade 9) Arab children studying at Arab schools in Kuala Lumpur-Malaysia. Data were collected via two questionnaires (one for loneliness and the other for self-esteem). The correlational data analysis yielded a negative correlation between loneliness and academic achievement while there is a positive correlation between self-esteem and achievement. Results also suggested that there is no correlation between students' gender, age, and academic achievement. Furthermore, the results revealed that self-esteem is a good predictor of achievement while loneliness and gender are not good predictors. The findings of the present study are discussed in relation to the relevant literature, taking into consideration the impact of children mental health on their academic achievement. Finally, recommendations for further research are presented.